Exploring the link between M1 macrophages and EMT of amniotic epithelial cells: implications for premature rupture of membranes - Yuhua Gao; Yanan Zhang; Ningning Mi; Wang Miao; Jingmiao Zhang; Yize Liu; Zhikun Li; Jiaxun Song; Xiangchen Li; Weijun Guan; Chunyu Bai (Journal of Nanobiotechnology)
Abstract Background Despite increasing evidence supporting the role of an amniotic epithelial-mesenchymal transition (EMT) in the premature rupture of membranes (PROMs), it remains unclear if extracellular vesicle (EV) derived from M1 macrophages play a critical role in triggering the EMT of amniotic epithelial cells (AECs). Results This study revealed that under inflammatory conditions, EV-miR-146a/155 from M1 macrophages could trigger EMTs and MMP-9 transcription in AECs, elevating the risk of PROM in both mice and humans. Introduction of EV-miR-155 led to inhibition of Ehf expression and reduced E-cadherin transcription in AECs. Meanwhile, EV-miR-146a activated the β-catenin/Tcf7 complex to promote the transcription of Snail, MMP-9, and miR-146a/155, inducing EMTs. Subsequently, EMT induction in AECs is associated with a loss of epithelial characteristics, disruption of cellular junctions, widening of intercellular spaces, and diminished biomechanical properties of the amniotic membrane. Conclusion Inflammatory stimulation prompts the polarization of macrophages in amniotic fluid into the M1 type, which subsequently secrete EVs laden with inflammatory miRNAs. These EVs trigger the EMT of AECs, causing the loss of their epithelial phenotype. Consequently, the biomechanical properties of the amnion deteriorate, ultimately leading to its rupture, posing risks relevant to pregnancy complications such as premature rupture of membranes. The results of this study provide insights into the pathogenesis of PROM and will aid in treatment development.